Avaliação da Aprendizagem na Disciplina Estrutura Política e Gestão Educacional: Um Estudo Comparativo entre os Cursos Presencial e Semipresencial da UFC/UAB - Sousa, Maria Iracema Pinho de (2012)
This study had the objective of investigating the process of teaching and learning in a Structure, Politics and Education Management (SPEM) course, trying to compare the blended course (which uses distance learning education – DLE) against the pure classroom course. This comparison was made using the results obtained through the application of an instrument with a evaluation scale about the relationship between the knowledge of the basic education legislation and other aspects that involve this course in the Federal University of Ceará regarding apprenticeship. Two DLE classes from the Language Bachelor’s were followed in the cities of Ipueiras and Russas along with other two, based in Fortaleza, under pure classroom teaching in different semesters. With this purpose a review was made on subjects such as DLE in Brazil, Cyberculture and Technology, Education Legislation and Learning Evaluation, conducting to deeper thoughts on the undergraduate teaching from different areas taking into account the need of some knowledge from them in aspects related to Education legislation with the perspective of their future actions in basic education. The investigation is of both qualitative and quantitative nature, in view of the analysis and search for understanding measurable educational phenomena from the observation of subjects involved in the process of teaching and learning during the course. The selected sample according to the nature of this study comprises undergraduate students from various semesters enrolled in the SPEM course from both the Federal University of Ceará and the Brazil Open University System, for a total of 81 individuals. Data collected revealed the necessity of reading and studying subjects from the SPEM classroom course related to educational legislation and a crucial point. From the results, a brief discussion was made on the aspects that involve the SPEM course in the curriculum at the undergraduate level, considering limits and possibilities of the evaluation in the classroom courses and through virtual means of learning